Evolutionary Interactive Bot for the FPS Unreal Tournament 2004 - Jiménez, José L.; Mora, Antonio M.; Fernández-Leiva, Antonio José (My University, 2015)
This paper presents an interactive genetic algorithm for generating a human-like autonomous player (bot) for the game Unreal Tournament 2004. It is based on a bot modelled from the knowledge of an expert human player. The algorithm provides two types of interaction: by an expert in the game and by an expert in the algorithm. Each one affects different aspects of the evolution, directing it towards better results regarding the agent’s humanness (objective of this work). It has been conducted an analysis of the experts’ influence on the performance, showing much better results after these interactions that the non-interactive version. The best bot were submitted to the BotPrize 2014 competition (which seeks for the best human-like bot), getting the second position
Keywords: Algoritmos genéticos; Videogame; Human-like behavior; Unreal Tournament; Interactive algorithm; Bio-inspired algorithms